Analysis of threats to South American flora and its implications for conservation - Ramírez Villegas, Julián Armando; Jarvis, Andy; Trouval, Jerry (Elsevier, 2012)
South America houses a significant proportion of the world's plant diversity and therefore merits conservation attention. However, ongoing habitat fragmentation, degradation and destruction of natural habitats threaten biodiversity. A set of seven threats to natural ecosystems derived from a previous study (Jarvis et al. 2010), combined with a dataset of occurrences from 16,339 species, and also with the World Database of Protected Areas were used to analyse the patterns of threats to flora in South America and its conservation. Species richness per ?50 km side cell ranged from 1 to 2149 taxa, but with most of the areas presenting between 1 and 58 taxa. Population accessibility, expansion of agriculture and grazing pressure were found to be the key drivers of immediate extinction risk. A considerable (78.4%) number of species presented at least one population under high threat due to the expansion and intensification of these anthropogenic activities. In addition, some 13.8% of the analysed species presented up to 80% of their populations at risk of extinction (high threat index). On the conservation side, 82.3% of the analysed taxa have at least one population occurring within a protected site. However, it is important to note that for a protected area system to be effective and efficient, the conservation of within-taxon genetic diversity is required. The expansion, monitoring and strengthening of 24 existing protected areas holding up to 70% of South American plant diversity is suggested; as is the revision of seven additional sites where up to 200 species not currently conserved are present. Critical areas to monitor, expand and strengthen are mainly located in the Ecuadorian and Colombian Andes, southern Paraguay, the Guyana shield, southern Brazil, and Bolivia.